Kebijakan Penyaluran Beras Sejahtera Madani di Kelurahan Pematang Pasir Kecamatan Teluk Nibung Kota Tanjungbalai - Sirait, Masitoh; Warjio, Warjio; Kadir, Abdul (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The purpose of this study is to describe the supporting and inhibiting factors in the implementation of the Madani Prosperous Rice Program in Pematang Pasir Subdistrict, Teluk Nibung Subdistrict, Tanjungbalai City. This research method uses qualitative research with a descriptive-analytical approach. The results showed that the limited time at the planning stage caused the implementation of Madani Prosperous Rice program to be "forced". These time limitations also influence the success of the implementation of each stage and the overall program. In targeting, mistargeting was encountered, although at a relatively low level. This is indicated by the existence of non-poor households who are recipients of Madani Prosperous Rice (leakage) and the existence of poor households that have not yet become recipients (undercoverage). For future management concepts, a household census is collected to collect household socio-economic data, including demographic structure and household characteristics, which are then used as basic information to conduct discriminant analysis to separate poor and non-poor populations. In addition it is necessary to conduct trials through small-scale pilot which need to be continuously evaluated, before the program is run nationally. It is recommended that the government design other programs that can empower the poor, so that they are not too dependent on government assistance programs.